Traumatic experience of residents of the de-occupied territories of Ukraine - Kuzikova , Svitlana Borysivna; Zlyvkov , Valerii Lavrentiiovych; Lukomska , Svitlana Oleksiivna (Insight: the psychological dimensions of society, 2023)
The article is devoted to clarifying the war-related traumatic experience of the residents in the de-occupied Kyiv and Kharkiv regions of Ukraine. The purpose of the research is to determine the traumatic experience of the residents in the de-occupied territories of Ukraine caused by the Russian-Ukrainian war. Methods. In this study, we compared the severity of post-traumatic stress disorder (PTSD) and traumatic grief among the respondents aged 14 to 70 years who were in the active combat zone and under temporary occupation in the Kyiv and Kharkiv regions of Ukraine. 394 respondents participated in the research. Participants were asked to describe their traumatic events using the questionnaires: International Trauma Questionnaire (ITQ), Traumatic Grief Inventory-Self Report Plus (TGI-SR+), Post-traumatic Stress Disorder Checklist for DSM-5 (PCL-5). Results. It was found that residents in the de-occupied territories of Ukraine are characterized by significant symptoms of PTSD, such as agitation and avoidance, traumatic grief expressed in excessive excitement, and traumatic loss has a moderate effect on the general adaptation of the respondent’ personality. In particular, agitation in the context of post-traumatic stress disorder and traumatic grief is more characteristic of teenagers and young people; young people are characterized by symptoms of avoidance and intrusions, people aged 31-50 years – by intrusions, and the oldest respondents – by excitation. Conclusions. This study shows that PTSD symptoms are more common for respondents over fifty years of age, who have deficit of internal and external resources. It has been proven that residents’ PTSD symptoms severity in the de-occupied Kharkiv region is statistically significantly lower than that of the residents’ of the de-occupied Kyiv region, this is due to longer occupation, and therefore, the emergence of PTSD symptoms is possible in a more delayed period.